2021
DOI: 10.1016/j.clae.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel water propelled, heating eye mask massager on tear film and ocular adnexa

Abstract: Purpose: to determine the effectiveness of the Aurai water propelled, heating Eye Massager (AEM) in managing dry eye disease and its effects on the ocular adnexa.Methods: This was a prospective, randomised cross-over study that enrolled 15 participants (aged 25.8 ± 5.45 years, 5 male). Participants wore a smart watch 24 hours a day to track their sleeping cycle and heart rate for 4 weeks, using the AEM twice a day for 2 of those weeks. A cycle of 6 minutes of a controlled heat and vibration pattern in the morn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Chen et al found [ 35 ] significantly higher SANDE scores in a sample of young women, mostly without dry eyes, and Kheirkhah et al [ 22 ] also found higher SANDE (67.5 ± 17.8) than OSDI (47.9 ± 23.2) scores in a sample of patients with meibomian gland dysfunction. In contrast, other reports have described lower SANDE scores than OSDI scores in dry eye patients [ 18 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Chen et al found [ 35 ] significantly higher SANDE scores in a sample of young women, mostly without dry eyes, and Kheirkhah et al [ 22 ] also found higher SANDE (67.5 ± 17.8) than OSDI (47.9 ± 23.2) scores in a sample of patients with meibomian gland dysfunction. In contrast, other reports have described lower SANDE scores than OSDI scores in dry eye patients [ 18 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 62%
“…Several questionnaires have been proposed to explore DES in clinical and research practice [ 7 , 8 , 9 , 10 , 11 ], but OSDI and SANDE have been widely used for decades [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The OSDI questionnaire, in conjunction with DED, has been recommended as the primary questionnaire for diagnosing DED by TFOS DEWIS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other simple treatments for dry eye disease include warming the meibomian glands. Microwave-heated compresses work well 340,341 and are better than the traditionally advocated water-warmed flannels, 342,343 as they maintain the required temperature 344 of approximately 40°C 345 ; however, there is still scope to refine the treatment protocol and to assess whether mechanical in-office [346][347][348] or portable devices we have evaluated 349 outperform simple approaches. We have shown that the meibomian glands do need to be more than 10% of their original length to have potential of expressing meibum.…”
Section: Technology-driven Enhancements In Ocular Surface Disease Dia...mentioning
confidence: 99%